Location Choice of Snatching Offenders in Chennai City - Kuralarasan, K. (Journal of quantitative criminology, 2022)
Objectives We aim to test the applicability of crime pattern theory in an Indian urban context by assessing the effects of offender residence, prior offending locations and presence of crime generators and crime attractors on where offenders commit offences. Methods The data comprise 1573 police-recorded snatching offenses committed by 1152 identified offenders across the 201 wards of Chennai City. We used discrete crime location choice models to establish the choice criteria that snatching offenders use when they decide where to offend. Data on the locations retail businesses, religious and transportation facilities were collected using Google location services. Results The results confirm that snatching offenders prefer to target locations closer to their residence and that they prefer to re-offend at or near their prior offending locations. The findings also demonstrate that some but not all crime attractors and generators influence the location choice of snatching offenders. Conclusions By replicating in an Indian context previously published crime location choice findings, our findings support the generality of crime pattern theory. We discuss limitations and make suggestions for future investigations.